EFFECT OF STANDARD TANNIN ON IN VITRO RUMEN METHANE REDUCTION AND RUMEN FERMENTATION CHARACTERISTICS - A. Bharathidhasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Methane is normally emitted by ruminants and represents a loss of feed energy by 8-12 %. Various feeding strategies are used to reduce the methane emission from ruminants for sustainable animal production. In this context an experiment was conducted to find out the effect of a standard tannin on rumen methane reduction and rumen fermentation characteristics for dairy cattle by in vitro gas production technique (IVGPT). The IVGPT was carried out by incubating the Cumbu Nappier hybrid (CO4) grass and rumen liquor with standard tannin at varying level viz. 0, 1.03, 2.06, 3.09 and 4.12 % of substrate in six replicates in shaking water bath for a period of 24 hours. After 24 hours the total gas production and pH were measured and methane was estimated in Gas Chromatography. The in vitro true dry matter digestibility (IVTDMD) was estimated and methane emission (ml) per 100 mg truly digested substrate was calculated. The rumen fermentation characteristics were also studied. The total gas production was significantly (p